Pedometers, the frustrating motivators: a qualitative investigation of users' experiences of the Yamax SW-200 among people with multiple sclerosis. Issue 3 (30th January 2022) - Fortune, Jennifer; Norris, Meriel; Stennett, Andrea; Kilbride, Cherry; Lavelle, Grace; Victor, Christina; De Souza, Lorraine; Hendrie, Wendy; Ryan, Jennifer
Abstract: Purpose: Self-monitoring may represent a mechanism to enhance physical activity among people with multiple sclerosis. To optimise activity monitoring as a behavioural tool to increase physical activity, user experience must be understood. This study evaluated user experience of the Yamax SW-200 Digi-walker pedometer in a group of people with MS. Methods: Semi-structured interviews were conducted with 15 adults who participated in a 12-week pedometer-supported behavioural change intervention, the iStep-MS trial. Interviews were audio-recorded and transcribed verbatim. Data were analysed using the Framework Method. Results: An overarching theme Pedometers, the frustrating motivators captures the complex and often contradictory experience of the pedometer. Sub-themes include: Increasing activity awareness, which describes the pedometer's utility in raising activity consciousness; Numeric motivation provides insight into dual motivating and demotivating experiences of using an objective feedback device; (Un) usability focuses on practical concerns encountered in the day-to-day use of the monitor. Conclusion: The Yamax SW-200 Digi-walker raised awareness and enhanced participant motivation to engage in physical activity. Accuracy and usability concerns highlighted warrant consideration in the selection of this pedometer within a population with multiple sclerosis. Trial registration: Changing physical activity behaviour in people with MS: the iStep-MS trial; ISRCTN15343862; https://doi.org/10.1186/ISRCTN15343862 Implications for rehabilitation: Use of self-monitoring tools such as pedometers can enhance physical activity awareness. Objective, numeric step count feedback is an effective motivational tool for physical activity. Accuracy and usability concerns may limit the value of the Yamax SW-200 Digiwalker for people with MS. Identification of individualised, reliable, usable and acceptable tools is important to ensure engagement with self-monitoring.